SOCIO-PSYCHOLOGICAL CONTENT ANALYSIS OF EGO-DEFENSE MECHANISMS IN A PERSONAL MYTH OF A STUDENT, FUTURE TRANSLATOR - ROTARU Silvia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The interpreter’s competence is determined by how accurately, without distortion, the translation is done. One of the reasons for distortion is socio-psychological. In the case of an emotionally incompetent Ego of the interpreter, ego-defence mechanisms operate and lead to complete or partial distortion in translation. Thus, Ego-defense mechanisms become a determinant of socio-emotional outsiderism. The aim of the article is to explore the problem of socio-emotional outsiderism and coping behavior as it’s opposite pole in a“Personal Myth”. In this context, the conditions of living the myth are examined, inter alia, in a personal myth. Hence, a content analysis of students’ “Personal Myth” is carried out, in order to identify the ego-defense mechanisms. To conclude, in the course of this study, the experience of catharsis while living emotionally the personal myth is a valid indicator of the Ego competence formation among future interpreters, which in its turn tells on more accuracy in their translation as the need to exploit ego-defense mechanisms is reduced.